Canva Sebagai Media Desain Untuk Promosi Content Creator - Lestari, Jemi; Octaviani, Vethy; Sari, Sapta (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
The design of content created by influencers and entrepreneurs to enhance performance and attract customer interest includes visual graphic design for logos or content creation. This study aims to determine if Canva as a design tool can be used for promotion by content creators. The principles of Visual Communication Design from Gestalt Theory include form similarity, pattern continuation, proximity, closure of form, and imagery. The research method used is descriptive qualitative. The technique for determining informants is purposive sampling from two content creator accounts, namely Anggel Kitty Store and Traccy.id in November 2023. The research findings are firstly, form similarity with the use of color in the design, both using visual messages in the design; secondly, the continuity of patterns in pictures, colors, and fonts in the design and the presence of informative messages; thirdly, the proximity of positions grouped according to type and function in the design, both using the logo layout in the design; fourth, closure of shape using sketch classes and squares in the design; and fifth, the core images used by content creators as visual messages in promotion. The designs created through Canva are used as promotional media for skincare, accessories, and makeup to be uploaded on Instagram, updated in Instagram stories, and to determine the design of posters to be promoted. Using Canva Pro is more appealing because it has more features than the standard Canva, and the designs also look better.